Fast Food Nation: What The All-American Meal is Doing to the World - Eric Schlosser (England Penguin Books, 2002)
DO YOU REALLY KNOW WHAT YOU'RE EATING WHEN YOU TUCK INTO THAT JUICY BURGER? Britain eats more fast food than any other country in Europe. It looks good, tastes good, and it's cheap. But the real cost never appears on the menu. Eric Schlosser's explosive bestseller, by turns funny and terrifying, tells the story of our love affair with fast food. He visits the lab that re-creates the smell of strawberries; examines the safety records of abattoirs; reveals why the fries taste so good and what really lurks between the sesame buns--and shows how fast food is transforming not only our diets but our world.
Keywords: Nonfiction; Food and Drink; Health; Sociology; Science; Politics; Global Citizenship (BIN1064-N)